A contingency management approach for treatment of methamphetamine use disorder and human immunodeficiency virus antiretroviral treatment adherence in pregnancy to prevent mother-to-child transmission: a case report - Suzanne Turner; Maya Nader; Erin Lurie (Journal of Medical Case Reports, 2022)
Abstract Introduction This review highlights the rising prevalence of methamphetamine use in pregnancy in North American and the difficulty of managing active human immunodeficiency virus infection in a pregnant woman while actively using methamphetamines. Multidisciplinary medical teams with knowledge of addiction medicine, infectious disease management, and pregnancy are needed to provide combined expert care to reduce the harms associated with substance use and improve adherence to antiretroviral treatment. We report the case of a treatment-naïve pregnant patient with human immunodeficiency virus who was actively using methamphetamines. The patient was able to initiate and adhere to antiretroviral treatment while taking a prescription stimulant in a contingency management paradigm. To the best of our knowledge, this is the first documented case of prescription stimulants being used in pregnancy to improve adherence to antiretroviral medications. Case presentation A 32-year-old white woman with untreated human immunodeficiency virus, a newly diagnosed pregnancy, and actively using methamphetamines presented to a drop-in combined prenatal care and addiction medicine clinic. After initiating a prescription amphetamine in a contingency management paradigm, she was adherent to human immunodeficiency antiretroviral treatment and had a fully suppressed viral load throughout the remainder of her pregnancy. Conclusion Active treatment of methamphetamine use disorders with prescription stimulants, coupled with contingency management, may represent a mechanism to engage patients in care and improve adherence to antiretroviral treatment (and prevent mother-to-child-transmission of human immunodeficiency virus).